Rhinitis medicamentosa - Martyna Byrska; Hanna Barska-Kobylińska; Marta Janura; Maja Weimann; Grzegorz Przywara; Oliwia Biegańska; Emilia Biczak; Ewa Katarzyna Malaka; Marlena Zubiak; Sara Langner (Journal of Education, Health and Sport)
Introduction: Rhinitis medicamentosa (RM) is a chronic inflammatory condition of the nasal mucosa caused by excessive use of topical nasal decongestants. This leads to tachyphylaxis, increased vascular permeability, chronic inflammation, and structural changes in the nasal mucosa, resulting in medication dependence and persistent nasal congestion.